1989
DOI: 10.1126/science.245.4917.513
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Cloud-Climate Feedback as Produced by 14 Atmospheric General Circulation Models

Abstract: Understanding the cause of differences among general circulation model projections of carbon dioxide-induced climatic change is a necessary step toward improving the models. An intercomparison of 14 atmospheric general circulation models, for which sea surface temperature perturbations were used as a surrogate climate change, showed that there was a roughly threefold variation in global climate sensitivity. Most of this variation is attributable to differences in the models' depictions of cloud-climate feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
270
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(274 citation statements)
references
References 13 publications
4
270
0
Order By: Relevance
“…Similarly, the effective climate sensitivities of AM2.1 (1.7 K), AM3 (2.0 K), and AM4.0 (1.9 K) over the historical period are significantly lower than the ECS of the parent AOGCMs (ESM2M (3.3 K) and CM3(4.8 K), computed from multimillennia equilibrium runs). Much of the uncertainty in the ECS has been attributed to cloud feedbacks (Bony & Dufresne, 2005;Cess et al, 1989). Despite large differences in ECS and effective climate sensitivities among AM2.1, AM3, and AM4.0, this study demonstrates that the cloudy response to changing SST patterns over the historical period is similar for these AGCMs.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Similarly, the effective climate sensitivities of AM2.1 (1.7 K), AM3 (2.0 K), and AM4.0 (1.9 K) over the historical period are significantly lower than the ECS of the parent AOGCMs (ESM2M (3.3 K) and CM3(4.8 K), computed from multimillennia equilibrium runs). Much of the uncertainty in the ECS has been attributed to cloud feedbacks (Bony & Dufresne, 2005;Cess et al, 1989). Despite large differences in ECS and effective climate sensitivities among AM2.1, AM3, and AM4.0, this study demonstrates that the cloudy response to changing SST patterns over the historical period is similar for these AGCMs.…”
Section: Discussionmentioning
confidence: 74%
“…We emphasize that the terminology "climate sensitivity" and "climate feedback parameter" here simply refer to measures of the change of radiative balance at TOA with fixed radiative forcing and prescribed SST. This method of computing climate sensitivity is in keeping with previous studies (Cess et al, 1989;Silvers et al, 2016;GA16), and we assume there is useful correspondence between the interaction of clouds and the TOA energy budget found here and in a fully coupled Earth system. For amip-piForcing experiments, F = 0, and the "effective" climate sensitivity can be inferred as F 2× ∕ , where F 2× is an appropriate representative value of radiative forcing due to doubled (relative to preindustrial) CO 2 concentrations (we use F 2× = 3.4 W m −2 , Flato et al, 2013).…”
Section: Methodology Of Analysismentioning
confidence: 96%
“…Clouds tend to dominate radiative fluxes and greatly influence regional and global climate [ Cess et al , 1989]. Cloud depths and droplet number concentrations ( N c ) determine the efficiency of radiation reflection.…”
Section: Introductionmentioning
confidence: 99%
“…Research over at least the past two decades has shown that an uncertain representation of clouds, specifically tropical low-level clouds, is currently the largest source of spread among state-of-the-art climate models [Cess et al, 1989;Bony and Dufresne, 2005;Stevens and Bony, 2013]. Specific limitations of modeled clouds include both features which differ from what one observes (e.g., ''too few, too bright,'' [Webb et al, 2001;Nam et al, 2012]) as well as features which are inadequately understood (e.g., controls on cloud vertical structure [Nuijens et al, 2015], and organization [Bretherton et al, 2005;Muller and Held, 2012;Wing and Emanuel, 2014]).…”
Section: Introductionmentioning
confidence: 99%